CAN THE CREDIBLE FISCAL POLICY MITIGATE THE TERMS OF TRADE FLUCTUATION? - Kuncoro, Haryo (Badan kebijakan Fiskal, 2017)
This paper examines the links between fiscal policy and terms-of-trade movement in the case of Indonesia over the period 2001-13. Unlike other researchers, this paper explores both the rules-based and discretionary fiscal policies. The earlier factor covers deficit rule and debt rule which are intended to measure the fiscal policy credibility. The later follows Fatás and Mihov (2003; 2006). The OLS estimation of quarterly data reveals that the less credible deficit rule policy and discretionary fiscal policy have a positive impact on the terms of trade. In contrast, the more credible debt rule policy and government size tend to depreciate the terms of trade. Those findings suggest that fiscal policy credibility does not matter in the context of international market. Furthermore, to mitigate the external risks, the government intervention to the international market debt should be limited.